Vaginal mucositis in patients with gynaecological cancer undergoing (chemo-)radiotherapy: a retrospective analysis. (18th August 2022) - Robijns, Jolien; Censabella, Sandrine; Bollen, Heleen; Claes, Stefan; Van Bever, Leen; Becker, Jindra; Pannekoeke, Luc; Bulens, Paul; Van de Werf, Evelyn
Abstract: The objective of this retrospective analysis was to determine the incidence and extent of vaginal mucositis (VM) in women with gynaecological cancer undergoing external (chemo)radiation therapy (CRT). A retrospective analysis was set up to collect data on the incidence and severity of VM in women treated with external pelvic RT for gynaecological cancer at the Jessa Hospital, Hasselt and ZOL, Genk, BE between January 2017 and June 2018. At the start and end of their external (C)RT, they rated the frequency and intensity of five common symptoms of VM. Thirty-three patients treated with RT for gynaecological cancer met the inclusion criteria. A non-negligible proportion of patients already experienced at least one VM symptom to any degree before the start of RT, a proportion that further increased towards the end of the RT (73%). At the end of RT, on average, about 25% of these patients reported moderate-to-severe symptoms (against about 7% before the (C)RT). These results suggest that VM is a rather frequent side effect in gynaecological cancer patients that aggravates during treatment up to a moderate severity level. Although the small sample size, these data highlight the need for attention to VM. Impact Statement: What is already known about this topic? Radiotherapy plays an important role in the treatment of gynaecological malignancies. A debilitating complication in patients undergoing pelvic radiotherapy is vaginal mucositis, an inflammation of the vaginal mucosal lining. To date, the incidence of vaginal mucositis is still not well documented. What this paper adds? A non-negligible proportion of patients already experienced at least one symptom related to vaginal mucositis before the start of radiotherapy. Most patients presented mild to moderate vaginal mucositis symptoms at the end of external pelvic radiotherapy. Burning sensation, pruritus, and pain were the most frequently documented radiotherapy-induced complications. The implications of this paper: Vaginal mucositis is an underrated side effect of pelvic radiotherapy that needs to be tackled multidisciplinary by a team of nurses, radiotherapists, oncologists, and gynaecologists. The team should tackle the complication from the start of radiotherapy by using the most appropriate measures. Due to a possible link between acute vaginal mucositis and late vaginal toxicity, the team needs to follow-up patient's post-radiotherapy to support patients in late complications and advise/encourage patients in performing vaginal dilatation to prevent vaginal stenosis.